Application of the log-linear analysis to choose determinants of disability among the elderly residents of south-eastern Poland - Ćwirlej-Sozańska, Agnieszka; Sozański, Bernard; Wilmowska-Pietruszyńska, Anna (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Many variables in research in the area of medical and health sciences are qualitative in nature. A common statistical tool used to analyze them is the χ2 test. However, it does not allow us to assess the relationship between a number of variables and distinguish the factors determining the investigated phenomenon. A more accurate tool is the log-linear analysis, which enable the researcher to evaluate the dependences and interactions between the studied variables. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Purpose: Description of the use of log-linear analysis on the example of the cross-sectional study on disability of the elderly. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: The assessment of disability and the choice of the factors that determine it was carried out on the results of a survey of 800 randomly selected people aged 71-80 years from the area of south-eastern Poland. The research tool was a WHODAS 2.0 questionnaire and a respondent’s particulars. The log-linear model was used for the analysis. In order to evaluate the fitting of the model, the Pearson’s χ2 and the χ2 maximum likelihood statistics, R2 and A coefficients were used. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: Education, adjustments of a house / flat, physical exercises have a significant impact on the prevalence of disability in the study group. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: The log-linear analysis allows us to determine the effect not only of individual variables on the formation of an independent variable, but also their interactions and the determination the odds occurrence of a dependent variable according to different qualitative categories of dependent variables. The information obtained in this way is a valuable clue to take practical action to decrease or increase the severity of the studied phenomenon.